Problem of preparation of future teachers to the use informatively communication technologies on the lessons of mathematics in 5–6 classes - Бурчак, Станіслав Олександрович; П’ятниця, Ольга Володимирівна (Pedagogy of Higher and Secondary Education, 2013)
Burchak S. A., Pyatnitsa O. V. Problem of preparation of future teachers to the use informatively communication technologies on the lessons of mathematics in 5–6 classes. The article is devoted the problem of preparation of future teachers to the use informatively communication technologies in the process of teaching of mathematics in 5-6 classes. In the article the offered system and methodical providing of stage-by-stage process of preparation of future teachers of mathematics is to the probed problem.